The human family tree [videorecording (DVD)] - Cohen, Chad; Wells, Spencer, 1969-; Bacon, Kevin, 1958- (National Geographic ; Distributed in the U.S.A. and Canada by Warner Home Video, 2009)
"Join geneticist Spencer Wells and a team from National Geographic's Genographic Project as they trace the human journey through time, from our origins in the heart of Africa to the ends of the world. Cutting edge science, coupled with a cast of New Yorkers -- each with their own unique genetic history -- helps paint a picture of these amazing journeys. The human family tree answers some of humanity's most burning questions -- who we are and where we come from -- and forces us to change how we think not only about our relationships with our neighbors, but ourselves"--Container.